Loss Aversion under Risk: The Role of Complexity - Tobias Cagala (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
In choice under risk, differences between alternative states of the world render choice environments complex. Moreover, they entail powerful experiences of loss if satisfaction falls short of prospective states that did not materialize. An increase in complexity, i.e. a larger number of differences, can have ambiguous effects on loss aversion. Complexity can direct the decision maker's attention to prospective experiences of loss but also requires a higher cognitive effort of weighting and comparing satisfaction in all states. This paper investigates empirically how loss aversion interacts with complexity. Structural estimates of preference parameters indicate an inverse-U shaped relationship between complexity and the weight of expected gain-loss utility in choice under risk.
Keywords: C91; D81; D84; 330